ダイ13ジ ナンキョク チイキ カンソクタイ ナツタイ ホウコク 1971-1972 - 清野, 善兵衛; セイノ, ゼンベイ; SEINO, Zenbei (国立極地研究所, 1974)
P(論文) Forty members of the 13th Japanese Antarctic Research Expedition left Tokyo on November 25th, 1971, aboard the icebreaker FUJI, under the command of Captain MAEDA. The expedition team was led by the author who also led the summer party of 10 members. Mr. KAWAGUCHI, deputy leader, also led the wintering party of 30 members at Syowa. The FUJI, equipped with two Sikorsky S-61A helicopters and one Bell 47G2A helicopter for polar operations, carried nearly 500 tons of cargo for the wintering party. Since the dry after the departure, scientific researches on board, comprising oceanography, biology, meteorology, gravity survey, radio wave propergation and cosmic ray, were performed according to the schedule. On December 16th, 1971, the FUJI left Fremantle and reached the ice edge on January 1st, 1972, approximately 40 miles north from Syowa. Since January 5th, the FUJI tried to break through the fast ice to approach Syowa, but her progress against the hard winter fast ice averaged only one mile a day. Fortunately, the weather condition was good enough for the flights of helicopters throughout the period, so the transportation of supplies for the station and scientific field studies was carried out efficiently. On February 20th, the 13th wintering party was organized to take the place of the 12th wintering party at Syowa Station. On February 23th, the FUJI at the location of 17 miles west-northwest of Syowa, directed her couise northward and started for home. However, on March 13th when she reached the edge of ice she met with closed pack ice (consolidated pack ice) as wide as 6 miles, and was forced to stay there. After two weeks of standstill, the closed pack ice was loosened suddenly on March 28th by the swell from northern water, so that the FUJI extricated herself out of the ice easily. The FUJI returned to Tokyo on May 16th via Cape Town and Jakarta. departmental bulletin paper